A Literature Review of the Implementation of Differentiated Learning in Indonesian Education Units - Devi Meika Sari; Firdaus Maulida; Jelita Puspita Ningrum Khoirunnisa; Siti Khoiriyatul Ummah; Setyo Admoko (Universitas Lambung Mangkurat, 2023)
The Merdeka Curriculum is currently implemented in Indonesia using a new paradigm of learning and assessment, namely learning that meets the learning needs of students. For this reason, differentiated learning is very suitable for the Education unit. The research examines the implementation of differentiated learning in the Indonesian Education Unit. This research is a literature review that involves reviewing related articles that aim to find scientific and theoretical studies. The author reviews 16 journals, consisting of 12 national journals and four international journals, with various methods to find out research results related to differentiated learning. The results showed that the advantages of implementing differentiated learning are that it can improve student learning outcomes, student learning motivation, understanding, and quality of student learning, it can accommodate students' learning needs by paying attention to their interests, profiles, learning styles, and learning readiness; and the independent curriculum can create active and creative learning and increase students' learning motivation.